Correlation and comparison of syndesmosis dimension on CT and MRI. (August 2016) - Wong, Fabian; Mills, Rebecca; Mushtaq, Nadeem; Walker, Roland; Singh, Samrendu K.; Abbasian, Ali
Highlights: Misdiagnosis of the distal tibiofibular syndesmotic injury could lead to significant long-term morbidity. Our results show that CT scan measurements of the distal tibiofibular joint are wider than and significantly different from that measured from MRI. We therefore recommend that when the widening found on a CT scan is minor or the diagnosis is equivocal, a contralateral comparative CT or an ipsilateral MRI scan is obtained to prevent misdiagnosis. To our knowledge, this is the first study to correlate CT and MRI findings of the distal tibiofibular joint. Abstract: Introduction: Various methods using CT scan have been described to diagnose distal tibiofibular syndesmotic injuries. However, CT scan does not take into account the amount of cartilage within the distal tibiofibular joint and could therefore lead to false positive results. We present the first study correlating the findings of the distal tibiofibular syndesmosis on CT and MRI scans. Methods: CT and MRI scan of consecutive patients over a period of 18 months, and of a time lapsed less than 12 months between the two imaging modalities, were reviewed. Measurements of the distal tibiofibular syndesmosis were taken according to a previously published study at the level of the distal tibial physeal scar. Results: Twenty-six ankles from 25 patients were included in this study for analysis. Significant difference between CT and MRI assessments in the overall distal tibiofibular dimensions and in the posterior distal tibiofibular distance for those ankles with evidence of osteoarthritis was found. Interclass correlation coefficients suggest that such methodology was reproducible and reliable. Conclusion: When the widening found on a CT scan is minor or the diagnosis is equivocal, a contralateral comparative CT or an ipsilateral MRI scan is recommended to prevent misdiagnosis. Level of evidence: Level IV.